2002
DOI: 10.1159/000058397
|View full text |Cite
|
Sign up to set email alerts
|

Carbamylated Hemoglobin as a Therapeutic Marker in Hemodialysis

Abstract: Carbamylation requires isocyanic acid derived from urea. Carbamylation of hemoglobin (Hb) produces carbamylated Hb (carbHb), which could serve as a marker of posttranslational protein modification possibly associated with such uremic complications as atherosclerosis. Since relative carbHb levels are determined by mean urea concentration and duration of exposure, they could be used to assess the adequacy of a patient’s hemodialysis (HD) regimen. We therefore determined the relationship between carbHb and urea k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…111 Others have similarly demonstrated carbamylated hemoglobin could be a more accurate indicator of average urea between hemodialysis sessions than the standard indices of dialysis adequacy, Kt/V and URR. 110,112 In contrast, in a study limited by sample size (n=7), Balion et al found significant variability over time in individuals’ carbamylated hemoglobin levels, with little association with markers of dialysis adequacy. 46 …”
Section: Pathogenesismentioning
confidence: 93%
“…111 Others have similarly demonstrated carbamylated hemoglobin could be a more accurate indicator of average urea between hemodialysis sessions than the standard indices of dialysis adequacy, Kt/V and URR. 110,112 In contrast, in a study limited by sample size (n=7), Balion et al found significant variability over time in individuals’ carbamylated hemoglobin levels, with little association with markers of dialysis adequacy. 46 …”
Section: Pathogenesismentioning
confidence: 93%
“…For instance, carbamylated hemoglobin may be evaluated by measuring globin ␤ chain N-terminal carbamyl-valine residue by HPLC/UV quantification of the valine hydantoin derivative obtained after acid hydrolysis (59 ). Carbamylated hemoglobin is considered a marker of chronic renal failure (60 ) and is known to interfere with Hb A 1c measurement in patients with renal diseases (61 ).…”
Section: Carbamylation-derived Productsmentioning
confidence: 99%
“…No correlations were observed between these two parameters, whereas cHb was previously found to be associated with Kt/V values [5,6]. However, the results associating cHb and Kt/V were somewhat controversial [22,25,26].…”
Section: Discussionmentioning
confidence: 87%
“…Thus, carbamylated proteins have been proposed as valuable markers for the follow-up of patients with CKD. The most classical example is carbamylated hemoglobin (cHb) which has been suggested as a potential marker for the adequacy of hemodialysis therapy in CKD [5][6][7] as well as for differentiating acute from chronic renal failure [8,9]. During the course of the last decade, the development of mass spectrometry-based methods has enabled the emergence of new markers related to the carbamylation process.…”
Section: Introductionmentioning
confidence: 99%